Penyuluhan Manajemen Kecerdasan Emosional Anak bagi Orang Tua di Sekolah Indonesia Kuala Lumpur Malaysia : Kolaborasi Pengabdian Internasional - Said, Ratna; Suryanti, Suryanti; Junaidi, Junaidi (Jurnal Pengabdian UNDIKMA, 2024)
This community service activity aims to increase parents' understanding of managing children's emotional intelligence during their growth period towards adolescence at the Kuala Lumpur Indonesian School (SIKL) in Malaysia. The method of implementing the service used interactive counselling, with the target being 30 parents of children at the Kuala Lumpur Indonesian School. The stages of this activity included initial needs analysis, preparation, implementation coordination, activity evaluation, and data analyzed descriptively. The results of this service activity showed that the level of parental understanding in children's emotional management increased significantly; this is proven by data on the level of parental understanding before counseling was carried out as follows: a) 6% understand how to manage emotions; b) 60.8% do not understand how to manage emotions; and c) 34.2% understand some of the emotion management. After carrying out the counseling, the following results were obtained: a) 56.7% knew and understood how to manage emotions; b) 6.7% did not understand how to manage emotions; and c) 36.6% understood some of emotion management. From these data, it can be concluded that parents' understanding of managing emotional intelligence in children has increased to 56.70%.